Individual growth of Drepanotrema cimex (Pulmonata: Planorbidae) from Arenalcito pond, natural reserve multiple uses Martin García Island, Buenos Aires, Argentina - Martin, Stella Maris (2013)
The species of the genus Drepanotrema, most of them endemic to the Neotropical region, belong to the Planorbidae. Of the nine species of this genus, six are found in Argentina. The present investigation analysed the individual growth of Drepanotrema cimex in Arenalcito pond (34°11' S, 58°15' W), Martín García Island Natural Reserve of Multiple Uses, Buenos Aires Province, Argentina. A total of 14 samples were collected (n = 1931) from February 2006 to June 2007. Five environmental variables were measured: water temperature, dissolved oxygen (mg L-1), electrical conductivity (p.S cm-1), total dissolved solids, and pH. The individual growth of the species was analysed mathematically by means of the von Bertalanffy equation, where: Lt = 5,6(1-e-2’0592 (t-0’293)). The parameter Lro was estimated by the Ford-Walford Method. The population of D. cimex was characterised by a complex and dynamic size structure throughout the annual cycle. The analysis ofthe curves revealedunimodal (2006) andpolymodal (April to June 2007) distributions, which pattern servedto identify the existence ofcohorts within the population studied.